A genetic screen pinpoints ribonucleotide reductase residues that sustain dNTP homeostasis and specifies a highly mutagenic type of dNTP imbalance. Issue 1 (20th November 2018) - Schmidt, Tobias T; Sharma, Sushma; Reyes, Gloria X; Gries, Kerstin; Gross, Maike; Zhao, Boyu; Yuan, Jui-Hung; Wade, Rebecca; Chabes, Andrei; Hombauer, Hans
Abstract: The balance and the overall concentration of intracellular deoxyribonucleoside triphosphates (dNTPs) are important determinants of faithful DNA replication. Despite the established fact that changes in dNTP pools negatively influence DNA replication fidelity, it is not clear why certain dNTP pool alterations are more mutagenic than others. As intracellular dNTP pools are mainly controlled by ribonucleotide reductase (RNR), and given the limited number of eukaryotic RNR mutations characterized so far, we screened for RNR1 mutations causing mutator phenotypes in Saccharomyces cerevisiae . We identified 24 rnr1 mutant alleles resulting in diverse mutator phenotypes linked in most cases to imbalanced dNTPs. Among the identified rnr1 alleles the strongest mutators presented a dNTP imbalance in which three out of the four dNTPs were elevated (dCTP, dTTP and dGTP), particularly if dGTP levels were highly increased. These rnr1 alleles caused growth defects/lethality in DNA replication fidelity-compromised backgrounds, and caused strong mutator phenotypes even in the presence of functional DNA polymerases and mismatch repair. In summary, this study pinpoints key residues that contribute to allosteric regulation of RNR's overall activity or substrate specificity. We propose a model that distinguishes between different dNTP pool alterations and provides a mechanistic explanation why certain dNTP imbalances are particularly detrimental.